Mis- and Disinformation About Covid-19 - Sabrina Heike Kessler; Philipp Schmid (University of Zurich, IKMZ - Department of Communication and Media Research, 2022)
Misinformation and disinformation pose major challenges to effective health communication around the globe during the Covid-19 pandemic. In this special issue, we present research on mis- and disinformation about Covid-19 in the European context and describe challenges and potential solutions for health communication. More specifically, the special issue features articles that analyse (a) the prevalence of mis- and disinformation beliefs about Covid-19 and their impact on individuals, as well as the drivers of these beliefs and (b) the effectiveness of potential prebunking and debunking interventions to combat mis- and disinformation. The articles demonstrate the relevance of political attitudes and media use as significant predictors of belief in health misinformation and tested a variety of effective interventions- from pausing to think critically to detailed debunking. Together, the collection of articles serves to support the evidence-based efforts of international organisations, governments, social media technology companies, and major academic institutions to address the problem of health mis- and disinformation.